Progress report on the single transducer ultrasonic thermometer using electrostatic actuator - Michal Voldán; Libor Husník; David Mahovský (Heliyon, 2024)
This article presents improvements to the practical acoustic thermometer of the Czech Metrology Institute that enable measurements with argon gas. Through a careful comparison with standard platinum resistance thermometers, the device shows its potential as a reference instrument for the calibration of industrial thermometers with traceability to the thermodynamic temperature scale. The extended temperature range, now from −80 to 80 °C, is characterized by the measurement uncertainty of well below 0.15 °C. Challenges arise above 100 °C, where the microphone approaches its maximum permissible temperature, which leads to discrepancies in the time of flight (τ) measurement results. The lower temperature limit is constrained by temperature-controlled enclosures, suggesting possible redesigns for future improvements. Modifications to the waveguide cover could enable isothermal measurements at higher pressures, which would allow calculation of the speed of sound (u0). In addition, the upper temperature limit could be extended by lengthening the waveguide or installing a special high-temperature microphone. These results underline the versatility of PAT and provide insights for further improving its effectiveness over a wider temperature range.